Surgical staging identifies occult metastases in over 50% of uterine-confined carcinosarcoma - William Vintzileos; Hannah Beer; David Miller; Jayanthi Lea (Gynecologic Oncology Reports)
Objective: To evaluate and define the proportion of clinically stage I Uterine Carcinosarcoma (UCS) patients who are upstaged to FIGO stages II-IVB following primary surgery based on final pathology. Methods: We performed a retrospective review of patients diagnosed and treated for UCS at our institution from 2009 to 2023. All patients who underwent primary surgery for UCS and had clinically stage I (uterine-confined) disease were included. Uterine-confined disease was determined based on pre-operative physical exam and imaging. The primary outcome was the proportion of patients who were upstaged after surgery. Results: Ninety-eight patients underwent primary surgery with a median age of 64 years (IQR 59–68). Twenty-six patients (26.6 %) had suspected extra-uterine disease based on pre-operative evaluation and were excluded. Seventy-two patients (73.4 %) had uterine-confined disease based on pre-operative exam/imaging and underwent staging surgery. Of the 72 patients with clinical stage I disease, 39 patients (54.2 %) were ultimately diagnosed with advanced disease (FIGO Stages II-IVB), while 33 patients (45.8 %) had confirmed early-stage disease on final pathology (FIGO Stages IA or IB). Surgical staging revealed the following: 15.4 % (n = 6) were upstaged to Stage II, 5.1 % (n = 2) to Stage IIIA, 5.1 % (n = 2) to Stage IIIB, 35.9 % (n = 14) to Stage IIIC1, 12.8 % (n = 5) Stage IIIC2, and 25 % (n = 10) to Stage IVB. Conclusion: More than 50% of patients with pre-operative “uterine-confined” carcinosarcoma were upstaged on final pathology, mostly commonly to Stage III. Our findings underscore the importance of surgical staging since upstaging carries critical prognostic information and implications for adjuvant treatment planning.